Boffin boy and the invaders from space - Orme, David; Richardson, Peter (Ransom Winchester, 2013)
Boffin Boy, the brilliant young inventor, faces an extraterrestrial threat when aliens invade Earth, determined to steal humanity's creativity. With his gadgets and clever strategies, he rallies his friends to outsmart the invaders, proving that imagination is the ultimate weapon against any challenge.